Modality Epistemic Adverb in “Mata Najwa” Episode of “PSBB Rasa Kompromi” - Viva Avitasari; Luluk Isani Kulup (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2021)
Media is a means of information that conveys a message about a problem that is being experienced. Mass media includes newspapers, magazines, radio, television, blogs on the internet, and others. On television, there are many versions of information delivery, one of which is talk shows. In a talkshow, there is the attitude of the speaker when discussing his opinion through the use of words, phrases and clauses that can be analyzed. The analysis in this study focuses on Epistemic Modality in a talkshow of Mata Najwa on Trans7. The thesis with the title Epistemic Modality in Najwa's Eye Impressions Episode